Determination of Heat Transfer Coefficient and Thermal Dispersion of a Representative Porous Structure Based on Pore Level Simulations. Issue 21 (29th November 2020) - Patel, Vipul M.; Talukdar, Prabal
Abstract: In the present work, pore level simulations were performed to calculate heat transfer coefficient and thermal dispersion coefficient of a consolidated porous structure. A three-dimensional cubic unit cell structure, made up of six cuboid struts was selected to represent the idealized porous structure. To analyze fluid flow and heat transfer through the porous structure, governing fluid flow and energy equations were solved using the finite-volume method. A parametric study was carried out to investigate the effects of Reynolds number, Prandtl number, and porosity on heat transfer coefficient of the considered structure. A separate parametric study explored the variation of stream-wise dispersion coefficient with Reynolds number, Prandtl number, thermal conductivity ratio of the solid and the fluid phase, and porosity. Finally, generalized correlations for both non-dimensional heat transfer coefficient and stream-wise dispersion coefficients were proposed. It is observed that the obtained heat transfer coefficient follows two distinct trend lines for both porosities considered in the present investigation. For the considered operating conditions, the stream-wise dispersion coefficient is found to be proportional to square of Peclet number.